The Attractions and Perils of Flexible Mortgage Lending - Garmaise, Mark J. (Review of Financial Studies, 2013)
A mortgage program that offered borrowers greater flexibility in the timing of repayments increased a bank's volume by over 35%. Loans in the program exhibited superior performance. Despite this, a regression discontinuity analysis shows that the causal impact of offering flexibility was to attract borrowers to the bank who experienced quadruple the average delinquency rate. These contrasting findings are driven by the fact that the bank engaged in ex post sorting of stronger borrowers into the flexible program. This sorting masked the ex ante adverse selection effects that offering flexibility had on the entire borrowing pool.